2008
DOI: 10.1002/qre.925
|View full text |Cite
|
Sign up to set email alerts
|

A clustering approach to identify the time of a step change in Shewhart control charts

Abstract: Control charts are the most popular statistical process control tools used to monitor process changes. When a control chart indicates an out-of-control signal it means that the process has changed. However, control chart signals do not indicate the real time of process changes, which is essential for identifying and removing assignable causes and ultimately improving the process. Identifying the real time of the change is known as the change-point estimation problem. Most of the traditional methods of estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…1 illustrates, another clustering method is introduced to change point estimation literature. In this regard, Ghazanfari et al [10] introduced a statistical-clustering approach to identify the time of step change in Shewhart control charts which is applicable to both normal and nonnormal processes in either phase-1 or 2. Their cluster settings subjected to the constraint that clusters can only contain adjacent samples.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…1 illustrates, another clustering method is introduced to change point estimation literature. In this regard, Ghazanfari et al [10] introduced a statistical-clustering approach to identify the time of step change in Shewhart control charts which is applicable to both normal and nonnormal processes in either phase-1 or 2. Their cluster settings subjected to the constraint that clusters can only contain adjacent samples.…”
Section: Related Workmentioning
confidence: 99%
“…Their cluster settings subjected to the constraint that clusters can only contain adjacent samples. In order to estimate change point, Ghazanfari et al [10] considered all possible positions of τ and assumed that the observations before τ to be in the in-control cluster and all the observations beyond it to be in the out-of-control cluster. They showed that their proposed can considered as effective as the other traditional methods and also better than them in some cases.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…While Samuel et al (1998a, b), Pignatiello and Samuel (2001), Ghazanfari et al (2008), Perry et al ( , 2007, Perry and Pignatiello (2005, Fahmy and Elsayed (2006), and Noorossana and Shadman (2009) proposed procedures to estimate the change point in the parameters of univariate distributions, Nedumaran et al (2000), Atashgar and Noorossana (2010), Niaki and Khedmati (2012, 2014a, and Sullivan and Woodall (2000) considered change-point estimations in the parameter vectors of multivariate distributions. However, in some applications, the quality of a process can be better characterized by a relationship between a response variable and one or more predictors.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…For example, Jann [4] developed an estimator for multiple changes using genetic algorithm or Ghazanfari et al [5] applied clustering method for change point estimation in Shewhart control charts, and Atashgar and Noorossana [6] used artificial neural network for this purpose.…”
Section: Introductionmentioning
confidence: 99%